Development of Psychosocial Telenursing Education Stigma of Suspected Covid-19 (Rapid Reactive) Patients - Tri Wahyuni; Parliani; Kharisma Pratama; Tutur Kardiatun; Nita Zulfia; Paudilah; Gmeliana Adha Sari (Britain International for Academic Research (BIAR) Publisher, 2021)
In the midst of the Covid-19 pandemic, there is one social phenomenon that has the potential to aggravate the situation, namely stigma in patients suspected of Covid-19 or rapid reactive results. The lab results have not actually confirmed that the patient is positive for Covid-19 but the social environment or negative associations of a person or group of people who experience symptoms or bear certain diseases result in stigma against a person. This study aims to find out how the experience and stigma in patients suspected of Covid - 19. This study uses qualitative approach method of phenomenological studies and in-depth interviews with telenursing. The number of participants in this study was 10 participants. This study obtained 5 themes, namely physiological experience, psychological experience, biological experience, sociological experience and spiritual experience. The high positive number of Covid-19 in Indonesia makes the emergence of negative stigma of society to patients exposed to Covid-19, not even just Patients who are positive of Covid-19 who get negative stigma, therefore for diagnostic enforcement it takes examination by Molecular Test: Real Time PCR (Polymerase Chain Reaction) method. The sample types used are bronchoalveolar lavage, nasopharyngeal or oropharyngeal swabs, sputum, tracheal aspirate, nasopharyngeal aspirate or nasal wash, and biopsy tissue including from the lungs. Real Time PCR check method is the golden standard for the enforcement of diagnostic Covid - 19.